Time and place: a new chronology for the origin of the broch based on the scientific dating programme at the Old Scatness Broch, Shetland - Dockrill, Steven J; Outram, Z; Batt, C M (Proceedings of the Society of Antiquaries of Scotland, 2007)
Iron Age studies in northern Britain have been dominated by one monument form, the broch. This focus on these monumental towers of the Atlantic Scotland, perhaps at the expense of other archaeological evidence, has brought about a strong division in the archaeological community. MacKie and Armit have both recently summarized the development of broch studies detailing the opposing arguments for the date of construction. In recent years archaeological evidence for these monuments has indicated an indigenous development rather than being associated with the movement of Iron Age peoples. This paper presents new chronological data for the construction of a Shetland broch and examines the archaeological repercussions for the ‘early’ chronology provided by these dates. Excavations at Old Scatness in the South Mainland of Shetland have revealed new evidence for a broch and defended Iron Age Village.